A philosopher gone wild: CSU professor makes peace between God and science — and wins the world's most generous prize - Campbell, Greg, interviewer and author; Rolston, Holmes, 1932-2025, interviewee (Colorado State University. Libraries, 2003)
Dr. Holmes Rolston is interviewed by Greg Campbell in April 2003. Dr. Holmes Rolston will receive the Templeton Prize, valued at more than $1 million, on May 7 in London's Buckingham Palace from Prince Philip. He will use the money to endow a chair in his name at his alma mater, Davidson College in North Carolina, in the fields of science and religion. His studies in philosophy of science, in evolutionary and ecosystem science, and as an accomplished biologist have made Rolston the leading voice for protecting biodiversity — not only out of respect for nature, but also due to religious obligation. He already has carved on his future tombstone this epitaph: "Philosopher Gone Wild." That's his life well-lived.
A philosopher gone wild - Greg Campbell interview
Rolston wins prize - Greg Campbell interview
Philosopher Gone Wild: CSU Professor makes peace between God and Science — and wins the world's most generous prize. This appeared in Weekly, April 16-22, 2003, front page and pages 14-15.
Keywords: Rolston, Holmes, 1932-2025